The Type of Feelings of Worthlessness That Poses a High Risk for Suicide in Depression and Why - Danica Janse van Vuuren (Philosophy of Medicine)
There is large consensus across clinical research that feelings of worthlessness (FOW) are one of the highest risk factors for a patient’s depression becoming suicidal. In this paper, I attempt to make sense of this empirical relationship from a phenomenological perspective. I propose that there are purely reactive and pervasive forms of FOW. Subsequently, I present a phenomenological demonstration for how and why it is pervasive FOW that pose a direct suicidal threat. I then outline criteria, contingent upon empirical verification, by which clinicians can more confidently identify when a patient’s FOW place them at high risk of suicide.